Classification of transaction costs of rent business entities - S.V. Bardash; Т.S. Osadcha (Економіка, управління та адміністрування)
The change of economic formation in the post-Soviet countries has led to the revision of the attitude to rent relations, as well as the assessment of their effectiveness. The latter is possible when transaction costs are taken into account and these transaction costs certainly arise in terms of rent relations. Currently, their composition, and especially in the implementation of rent relations, remains undisclosed. The article is aimed at solving this problem, as well as outlining ways to reflect transaction costs in the accounting system. Thus, the research in this direction is relevant and promising. The purpose of the article is to identify and classify transaction costs in the system of rent relations. The methodological basis of the study is the dialectical method of knowing the essence of rent relations and measures to improve them; bibliographic method for identification of transaction costs in the context of theories of ownership, institutionalism, agency relations and collaboration alliances as a theoretical basis for the implementation of rent relations; comparative analysis of the economic essence, causes and classification of transaction costs; abstract-logical method for substantiation of basic theoretical positions, formulation of conclusions; modeling method for constructing the classification of transaction costs of rent business entities. Based on the study of recent publications, the existing approaches to determining the nature of transaction costs are summarized, the multivariate classification is identified, and the classification of transaction costs arising within the rent relations and which can be used as a basis for their reflection in accounting. The practical significance of the study is to develop the classification of transaction costs, which simplifies their identification and attribution to different stages of the implementation of rent relations.